Analisis Formula Teks Pantun Tradisi Lisan Cacapan Masyarakat Melayu di Lubuklinggau - Juita, Hartati Ratna (Universitas Muhammadiyah Surabaya, 2025)
The cacapan tradition, as an integral part of Malay culture, plays a significant role in conveying moral messages and cultural values through the use of pantun. This study aims to analyze the text formula in the performance of the cacapan tradition, focusing on the structure of pantun, rhyme patterns, and the messages contained within. The research method used is a qualitative approach, including participatory observation, in-depth interviews, text analysis, and literature review. The results show that pantun in the cacapan tradition is not just a ritual, but also a communication medium that connects spiritual, social, and cultural values between the older and younger generations. The text structure of pantun in the cacapan ceremony consists of opening, feeding, giving a drink, cacapan, prayers, and closing, each with its unique and rhythmic text formula. Analysis of the text formulas in various sequences of traditional ceremonies, particularly in the feeding event, reveals how pantun is used as a medium for conveying messages rich in cultural and religious values. Pantun beginning with bismillah highlights the importance of starting every activity by mentioning the name of Allah, in accordance with Islamic teachings.